Implementation of Nutrition Education Toward Controlling Blood Glucose Levels of Diabates Mellitus (DM) Patients - Azahra, Tarisa; Fitriani, Ade; Hidayat, Nur (KIAN JOURNAL, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder with multiple etiologies characterized by blood sugar levels exceeding normal limits. The prevalence of DM continues to increase globally, nationally, and locally, including in the working area of the Cigembor Community Health Center, Ciamis Regency. The primary issue identified is non-compliance with dietary recommendations due to low nutritional literacy and the absence of effective and sustained education. The intervention implemented is structured nutritional education aimed at fostering healthy eating behaviors to control blood glucose levels and prevent complications. Objective: This study aims to implement the nursing process with a focus on the structured, continuous, and patient-centered implementation of nutrition education in controlling blood glucose levels in DM patients. Method: This study used a descriptive method with a case study design through a nursing care approach, starting from assessment, formulating diagnoses, planning, implementing nutrition education to control blood glucose levels in patients with diabetes mellitus, and evaluation. Results: After three days of education, it was found that patients with diabetes mellitus who complained of dizziness, fatigue, decreased appetite, and high blood glucose levels were diagnosed with unstable blood glucose levels, with a focus on the implementation of nutrition education. Evaluation results showed a decrease in blood glucose levels to 213 mg/dL, improved appetite, and reduced complaints of dizziness. Conclusion: The implementation of nutrition education has proven effective in controlling blood glucose levels and improving patients' nutritional status.